A history of women in Russia : from earliest times to the present - Clements, Barbara Evans, 1945- (Indiana University Press, 2012)
"Synthesizing several decades of scholarship by historians East and West, Barbara Evans Clements traces the major developments in the history of women in Russia and their impact on the history of the nation. Sketching lived experiences across the centuries, she demonstrates the key roles that women played in shaping Russia's political, economic, social, and cultural development for over a millennium. The story Clements tells is one of hardship and endurance, but also one of achievement by women who, for example, promoted the conversion to Christianity, governed estates, created great art, rebelled against the government, established charities, built the tanks that rolled into Berlin in 1945, and flew the planes that strafed the retreating Wehrmacht. This daunting and complex history is presented in an engaging survey that integrates this scholarship into the field of Russian and post-Soviet history"--Provided by publisher.